Cost of Young Adults - Suzanna Smith (EDIS)
FAR0071, a 2-page transcript of the Family Album Radio Program broadcast by Suzanna Smith, provides research-based information on the types of contributions parents make for young adult children to help them get started. Includes references. Published by the UF Department of Family Youth and Community Sciences, March 2009.